Antibacterial Activity of Hand Sanitizer of Bay Leaf Extract (Syzgium polyanthum) on Staphyloccocus epidermidis Growth - Maramis, Arnetta Yolanda; Asri, Mahanani Tri (LenteraBio : Berkala Ilmiah Biologi, 2022)
Staphyloccous epidermidis is a bacterium that causes opportunictic infections and live on top of human’s hands. The growth of S. epidermidis can be inhibited by washing hands. However, this method can’t be done when there are no water and soap around. Hand sanitizer is an alternative for wiping those bacteria away. Bay leaf (Syzygium polyanthum) is a natural ingredient that contains flavonoid, essential oils, and tannins as antibacterial agent. The purpose of this study was to determine the antibacterial activity of hand sanitizer from bay leaf extract and to determine the most effective concentration in inhibiting S. epidermidis growth. A Completely Randomized Design (CRD) is used as a method. The concentrations of bay leaf extract used for hand sanitizer are 15%, 20%, 25%, and 30%. SNI standard hand sanitizer and distilled water are used for controls. The results were analyzed by Kolmogorov-Smirnov test, one way Anova test and Duncan test. Duncan test result is showed the most effective bay leaf extract hand sanitizer to inhibit the growth of S. epidermidis bacteria was a concentration of 30% with an inhibition zone of 33,25 ± 1,25 mm.